A canine distemper virus seroprevalence study of dogs on three islands in the Torres Strait region, Australia. Issue 8 (23rd June 2020) - Ruffalo, G; Byers, M; Ward, MP
Abstract : Canine distemper virus (CDV) can cause mortality in domestic dogs, which is easily prevented by the consistent application of vaccination protocols. The aim of this study was to determine if the dog populations of three strategically located islands in the Torres Strait of Australia, adjacent to Papua New Guinea, are infected by CDV. Eighty‐four serum samples were collected from 70 dogs resident on Saibai, Dauan and Boigu Islands during 2017–2018. Sera were tested for CDV antibodies by a virus neutralization test (VNT). Overall, 7 (8.3%) sera from 6 (8.6%) dogs resident on all three islands were test positive. VNT titres ranged from 20 to >1280. Male adult dogs were more commonly seropositive than female and juvenile dogs. Considering the origin and age of test positive dogs, and veterinary visits to these islands, it was concluded that there is evidence of exposure to a field strain of CDV – rather than previous vaccination – in 4 of the 70 dogs (5.7%) tested in this study. Given the strategic location of these islands in a zone of high biosecurity risk, ongoing surveillance of pathogens such as CDV could inform on potential disease spread pathways in this region. In addition, the presence of high serological titres in the apparent absence of clinical disease requires further investigation.